2023
DOI: 10.3389/fmicb.2022.1072140
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of lactic acid bacteria, microbial community and fermentation dynamics of native grass silage prepared in Inner Mongolian Plateau

Abstract: IntroductionTo prepare high-quality silage, we studied the chemical composition, silage fermentation, characterization, and identification of lactic acid bacteria (LAB) associated with the silage fermentation of native grass on the Inner Mongolian Plateau.MethodsLAB were isolated from fresh native grass and their silage, and silages were prepared using a small-scale fermentation system with 2–3 cm length in plastic bags.ResultsThe dominant species of native grasses used were Stipa baicalensis, Leymus chinensis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Subsequently, with the increase of moisture, the growth of Leucococcus was inhibited and the pH increased slightly, and the inhibition of Escherichia coli such as Serratia marcescens was weakened, and it competed with Lactobacillus and Leucococcus marcescens for nutrients, resulting in Escherichia coli such as Serratia marcescens becoming the dominant genus ( Heron et al, 2010 ; Weyker et al, 2016 ). Hou et al (2022) studied the changes in microbial communities during silage fermentation in native forages on the Inner Mongolian plateau, and their results also indicated that the abundance of Leucococcus significantly decreased with the increase in forage moisture.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, with the increase of moisture, the growth of Leucococcus was inhibited and the pH increased slightly, and the inhibition of Escherichia coli such as Serratia marcescens was weakened, and it competed with Lactobacillus and Leucococcus marcescens for nutrients, resulting in Escherichia coli such as Serratia marcescens becoming the dominant genus ( Heron et al, 2010 ; Weyker et al, 2016 ). Hou et al (2022) studied the changes in microbial communities during silage fermentation in native forages on the Inner Mongolian plateau, and their results also indicated that the abundance of Leucococcus significantly decreased with the increase in forage moisture.…”
Section: Discussionmentioning
confidence: 99%
“…LA is a major component of grass silage leachate at a typical concentration range between 22 and 38 g/L [12]. Since, a consortium of microorganisms is growing during the ensiling process both isomers D-and L-LA are present in the grass silage leachate [13,14]. Towards recovering LA from grass silage leachate, Ecker et al developed a LA recovery process that consisted of UF, two-step NF, ED, and reverse osmosis (RO) processes [15].…”
Section: Introductionmentioning
confidence: 99%